A two-nuclease pathway involving RNase H1 is required for primer removal at human mitochondrial OriL. Issue 18 (8th August 2018) - Al-Behadili, Ali; Uhler, Jay P; Berglund, Anna-Karin; Peter, Bradley; Doimo, Mara; Reyes, Aurelio; Wanrooij, Sjoerd; Zeviani, Massimo; Falkenberg, Maria
Abstract: The role of Ribonuclease H1 (RNase H1) during primer removal and ligation at the mitochondrial origin of light-strand DNA synthesis (OriL) is a key, yet poorly understood, step in mitochondrial DNA maintenance. Here, we reconstitute the replication cycle of L-strand synthesis in vitro using recombinant mitochondrial proteins and model OriL substrates. The process begins with initiation of DNA replication at OriL and ends with primer removal and ligation. We find that RNase H1 partially removes the primer, leaving behind the last one to three ribonucleotides. These 5′-end ribonucleotides disturb ligation, a conclusion which is supported by analysis of RNase H1-deficient patient cells. A second nuclease is therefore required to remove the last ribonucleotides and we demonstrate that Flap endonuclease 1 (FEN1) can execute this function in vitro . Removal of RNA primers at OriL thus depends on a two-nuclease model, which in addition to RNase H1 requires FEN1 or a FEN1-like activity. These findings define the role of RNase H1 at OriL and help to explain the pathogenic consequences of disease causing mutations in RNase H1.